A cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation 1-x Ce x O2 thin film, preparation method and application

By introducing zirconia ZrO2 intercalation into the Hf1-xCexO2 film, the problem of insufficient ferroelectric performance and durability of the existing HfO2-based ferroelectric film is solved, and the ferroelectric performance and leakage current performance of the film is significantly improved, which is suitable for the application of new microelectronic devices.

CN116514157BActive Publication Date: 2025-04-08UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310305928.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2025-04-08
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

The existing HfO2-based ferroelectric films have shortcomings in ferroelectric performance and durability, resulting in high power consumption and poor reliability in their applications in microelectronic devices.

Method used

A cerium-hafnium oxygen Hf1-xCexO2 film with zirconia ZrO2 intercalation was used. The sols of Hf1-xCexO2 and ZrO2 were respectively coated on the substrate, and the pyrolysis treatment was performed and the spin coating and pyrolysis treatment was repeated to form a preset thickness of HCO film with ZrO2 intercalation.

Benefits of technology

It significantly improves the ferroelectric performance and leakage current performance of the film, improves the stability and reliability of the device, and is suitable for low power consumption and high reliability applications of new microelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116514157B_ABST
    Figure CN116514157B_ABST
Patent Text Reader

Abstract

The present invention relates to a cerium hafnium oxide (Hf) with zirconium oxide (ZrO2) intercalation layer. 1‑x Ce x O2 film, preparation method and application, the method comprising: preparing Hf 1‑x Ce x O2 (HCO) sol and ZrO2 sol; spin coating the HCO sol and ZrO2 sol on a substrate in different orders to obtain a wet film; pyrolyzing the wet film and finally annealing and crystallizing it to obtain a cerium hafnium oxide Hf with a zirconium oxide intercalation layer. 1‑x Ce x O2 film. The present invention introduces a high dielectric ZrO2 intercalation layer into the HCO film and adjusts the intercalation position to obtain high-performance films with different ZrO2-HCO stacks. Compared with the prior art, the ferroelectric properties and / or leakage properties of the film prepared on the heavily doped Si substrate are significantly improved; on the flexible mica substrate, the addition of the ZrO2 intercalation layer can also significantly improve the ferroelectric properties of the film; and the preparation method of the present invention is simple, the content of the added elements is flexible and controllable, the success rate of the film preparation is high, the repeatability is good, and it is suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microelectronic devices, and specifically relates to a cerium hafnium oxide Hf with a zirconium oxide ZrO2 intercalation layer. 1- x Ce x O2 thin film, preparation method and application. Background Art

[0002] Ferroelectric materials, that is, materials that have spontaneous polarization within a certain temperature range and can change direction under the action of an external electric field, have broad application prospects in data storage, sensors, and actuators. Doped hafnium oxide HfO2 can form a metastable orthorhombic phase (i.e., ferroelectric phase) with a non-centrosymmetric structure, showing excellent ferroelectric properties. Compared with traditional oxide perovskite ferroelectric materials, fluorite-structured HfO2-based ferroelectrics have high compatibility with CMOS processes, good miniaturization, low operating voltage, moderate polarization intensity, and high radiation resistance. It is an extremely ideal new ferroelectric material, preparing for the industrial application of the next generation of high-density, non-volatile ferroelectric memory.

[0003] In order to stabilize the HfO2 ferroelectric phase and obtain excellent ferroelectric properties, Hf 1-x Ce x Research on O2 (HCO) solid solution films has been carried out. Compared with other element doped solid solutions, HCO ferroelectric films can effectively overcome the wake-up effect commonly found in HfO2-based films due to phase evolution, defect redistribution, etc., thereby improving the stability of device operation and are a strong candidate material for fluorite-type ferroelectrics. However, ferroelectric properties and durability are still the biggest shortcomings of HfO2-based films. In order to further improve the ferroelectric properties of HCO solid solution films, reduce leakage current, and ensure their low power consumption and high reliability applications in new microelectronic devices, it is urgent to optimize the preparation of films. Summary of the invention

[0004] In order to overcome the above problems in the prior art, the present invention provides a cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer. 1-x Ce x O2 film, preparation method and application are used to solve the above problems existing in the prior art.

[0005] A cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation 1-x Ce x A method for preparing an O2 thin film, the method comprising the steps of:

[0006] S1. Mix hafnium acetylacetonate, acetic acid, cerium nitrate hexahydrate and a chelating agent to obtain Hf 1-x Ce x O2(HCO) sol, where 0 <x<1;

[0007] S2. The zirconium acetylacetonate, acetic acid and a chelating agent are mixed to obtain a ZrO2 sol;

[0008] S3. applying the HCO sol and the ZrO2 sol on a substrate to obtain a wet film;

[0009] S4. pyrolysis treatment of the wet film;

[0010] S5. Based on step S4, repeat steps S3 and S4 to obtain a cerium hafnium oxide (Hf) layer with a zirconium oxide ZrO2 intercalation layer of a preset thickness. 1-x Ce x O2) film.

[0011] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein S1 specifically includes:

[0012] S11. Dissolve hafnium acetylacetonate in acetic acid solution, stir at 40-60°C for 10-30 min, and dissolve all the solute until it is clear;

[0013] S12. Weigh a certain amount of cerium nitrate hexahydrate into the solution obtained in S11, stir at room temperature for 10-30 minutes, and wait until the solute is completely dissolved and clear;

[0014] S13. Add an appropriate amount of chelating agent to the solution obtained in S12, heat in a water bath for 20-40 min, stir at room temperature for 4-8 h, and obtain HCO sol after aging.

[0015] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein S2 specifically includes:

[0016] S21. Take zirconium acetylacetonate as the solute, dissolve it in acetic acid solution, stir at 40-60°C for 10-30min, and dissolve all the solute until it is clear;

[0017] S22. Add an appropriate amount of chelating agent to the solution obtained in S21, heat in a water bath for 20-40 minutes, stir at room temperature for 4-8 hours, and obtain ZrO2 sol after aging.

[0018] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the chelating agent is acetylacetone.

[0019] According to the above aspects and any possible implementation, there is further provided an implementation, further comprising S6. adding the cerium hafnium oxide Hf with the zirconium oxide ZrO2 intercalation layer of the preset thickness 1-x Ce x The O2 film is subjected to high temperature annealing treatment in a certain gas atmosphere.

[0020] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the substrate is a heavily doped Si substrate or a flexible mica substrate.

[0021] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the preset film thickness is 50 to 100 nm.

[0022] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the value range of x is 0.11 to 0.16.

[0023] The present invention also provides a cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer. 1-x Ce x O2 film, the film is prepared by the preparation method.

[0024] The present invention also provides a cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer. 1-x Ce x Application of O2 thin film in new ferroelectric memory.

[0025] Beneficial Effects of the Invention

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) Compared with the existing technology, the ferroelectric properties and leakage current of the film on the heavily doped Si substrate have been significantly improved.

[0028] (2) On a flexible mica substrate, the addition of ZrO2 to the HCO film can significantly improve the ferroelectric properties of the film.

[0029] (3) The preparation method of the present invention is extremely simple, the content of the added elements is flexible and controllable, the success rate of film preparation is high, and the repeatability is good.

[0030] (4) The preparation method of the present invention only requires simple processes and low-cost equipment, and has simple environmental requirements, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a flow chart of the method of the present invention;

[0032] Figure 2 (a), (b) and (c) are schematic diagrams of different structures of the film of the present invention;

[0033] Figure 3 Schematic diagram of polarization-voltage curves of HCO thin films with or without intercalation and intercalation at different positions on heavily doped Si substrates constructed according to comparative examples and embodiments;

[0034] Figure 4 Schematic diagram of leakage current curve of HCO thin film with or without intercalation layer and intercalation layer at different positions on heavily doped Si substrate constructed according to comparative examples and embodiments;

[0035] Figure 5 Schematic diagram of polarization-voltage curves of HCO films on flexible mica substrates with thin ZrO2 intercalation layers in the middle and at the bottom and without intercalation layers, constructed according to comparative examples and embodiments. DETAILED DESCRIPTION

[0036] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific implementation methods described below, and similar technologies and methods should be considered to be within the scope of protection of the present invention. In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.

[0037] It should be clear that the embodiments described in the present invention are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0039] like Figure 1 As shown, the present invention is a cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation 1-x Ce x Preparation method of O2 thin film, cerium hafnium oxide (Hf O2) with zirconium oxide ZrO2 intercalation layer 1-x Ce x The HCO thin film with ZrO2 intercalation is also referred to as HCO thin film with ZrO2 intercalation, HCO thin film or thin film below, which are all thin films prepared by the method of the present invention, the method comprising the steps of:

[0040] S1. Mix hafnium acetylacetonate, acetic acid, cerium nitrate hexahydrate and a chelating agent to obtain Hf 1-x Ce x O2(HCO) sol, where 0 <x<1;

[0041] S2. The zirconium acetylacetonate, acetic acid and a chelating agent are mixed to obtain a ZrO2 sol;

[0042] S3. applying the HCO sol and the ZrO2 sol on a substrate to obtain a wet film;

[0043] S4. pyrolysis treatment of the wet film;

[0044] S5. Based on step S4, repeat steps S3 and S4 to obtain a cerium hafnium oxide Hf with a preset thickness of zirconium oxide ZrO2 intercalation layer. 1-x Ce x O2 film;

[0045] S6. The cerium hafnium oxide Hf with a preset thickness of zirconium oxide ZrO2 intercalation 1-x Ce x The O2 film is subjected to high temperature annealing treatment in a certain gas atmosphere.

[0046] Preferably, the S1 specifically includes:

[0047] S11. Dissolve hafnium acetylacetonate in acetic acid solution, stir at 40-60°C for 10-30min, dissolve all the solute until clear, preferably at 50°C for 20min;

[0048] S12. Weigh a certain amount of cerium nitrate hexahydrate into the solution obtained in S11, stir at room temperature for 10-30 minutes, until the solute is completely dissolved and clear, preferably 20 minutes;

[0049] S13. Add an appropriate amount of chelating agent to the solution obtained in S12, heat in a water bath for 20-40 min, stir at room temperature for 4-8 h, and age to obtain HCO sol, preferably for 30 min, 6 h.

[0050] Preferably, the S2 specifically includes:

[0051] S21. Zirconium acetylacetonate is used as a solute and dissolved in an acetic acid solution. The solution is stirred at 40-60°C for 10-30 min until the solute is completely dissolved and clarified. Preferably, the solution is dissolved at 50°C for 20 min.

[0052] S22. Add an appropriate amount of chelating agent to the solution obtained in S21, heat in a water bath for 20-40 minutes, stir at room temperature for 4-8 hours, and age to obtain ZrO2 sol, preferably for 30 minutes and 6 hours. The steps of S1 and S2 are not in any particular order and can be performed simultaneously.

[0053] Preferably, S3 further comprises: ultrasonically cleaning the substrate with acetone and anhydrous ethanol for 30 minutes respectively to remove oil stains and impurities on the surface of the substrate.

[0054] Preferably, the chelating agent is acetylacetone.

[0055] Preferably, the substrate is a heavily doped Si substrate or a flexible mica substrate.

[0056] Preferably, the preset thickness is 50-100 nm.

[0057] Preferably, the value range of x is 0.11 to 0.16.

[0058] Specifically, the preparation process of the present invention is as follows:

[0059] (1) Dissolve hafnium acetylacetonate in acetic acid solution first, stir at 50 °C for 20 min until all solutes are dissolved to clarity.

[0060] (2) Weigh a certain amount of cerium nitrate hexahydrate and pour it into the solution of (1), stir at room temperature for 20 min until all solutes are dissolved to clarity.

[0061] (3) Add an appropriate amount of acetylacetone as a chelating agent to the solution of (2), heat in a water bath at 30 min, then stir at room temperature for 6 h, and obtain Hf 1-x Ce x O2(HCO) sol, where 0 < x < 1; the HCO sol prepared by steps (1)-(3) of the present invention is stable, and compared with other methods, the prepared sol is not easy to settle.

[0062] (4) Use zirconium acetylacetonate as the solute, dissolve it in acetic acid solution, stir at 50 °C for 20 min until all solutes are dissolved to clarity.

[0063] (5) Add an appropriate amount of acetylacetone as a chelating agent to the solution of (4), heat in a water bath at 30 min, then stir at room temperature for 6 h, and obtain ZrO2 sol; the ZrO2 sol prepared by (4)-(5) of the present invention is stable, and compared with other methods, the sol is not easy to settle.

[0064] (6) Spin-coat the above-mentioned HCO sol and ZrO2 sol on different types of substrates in different orders to obtain a wet film.

[0065] (7) Perform pyrolysis treatment on the wet film.

[0066] (8) On the basis of step (7), repeat steps (6) and (7) to obtain a film with a preset thickness.

[0067] (9) Anneal the film with the preset thickness at high temperature in an N2 atmosphere to obtain the HCO film with ZrO2 interlayers, and this film is a solid solution dielectric film.

[0068] Preferably, in step (2), the value of x is 0.11 - 0.16.

[0069] Preferably, in step (3), the water bath temperature range is 50 - 70 °C.

[0070] Preferably, in step (3), the aging process of the HCO sol is carried out by standing at room temperature for 24-72 hours.

[0071] Preferably, in step (3), the HCO sol concentration is 0.1-0.3 mol / L.

[0072] Preferably, in step (5), the concentration of ZrO2 sol is 0.1-0.3 mol / L.

[0073] Preferably, in step (6), the HCO sol is spin-coated at 300-500 r / s for 10-15 s, so that the sol is tightly combined with the substrate at a low speed, so that the prepared film is smoother. Then, the ZrO2 sol is spin-coated at 3000-3500 r / s for 20-30 s to achieve the required thickness of each layer of the film to obtain a wet film; using the same spin-coating requirements as the HCO sol, the ZrO2 sol is spin-coated at 300-500 r / s for 10-15 s and at 3500-4500 r / s for 20-30 s to obtain a wet film.

[0074] Preferably, between steps (5) and (6), the method further includes: cleaning the substrate with a corresponding solvent to remove oil stains and impurities on the surface of the substrate to facilitate subsequent spin coating operations.

[0075] Preferably, in step (7), the wet film is subjected to pyrolysis treatment, and the operating steps are: keeping the temperature at 160-200°C for 2-4 minutes, and then heating to 300-350°C for 2-4 minutes. Under the above reaction conditions, the organic matter in the wet film can be completely decomposed, leaving only the required material elements.

[0076] Preferably, in step (8), the preset thickness of the HCO film is 50-100 nm, and the thickness of the spin-coated ZrO2 intercalation layer is 8-12 nm.

[0077] Preferably, in step (8), the spin coating and thermal decomposition can be repeated 5-8 times to obtain a film of a preset thickness.

[0078] Preferably, in step (9), the film of preset thickness is subjected to high temperature annealing crystallization treatment in a N2 atmosphere, and the operation steps are: keeping the temperature at 350-400°C for 3-5 minutes, then heating to 600-800°C and keeping the temperature for 3-5 minutes. The hafnium in the film may be recrystallized when annealed at the above temperature of 600-800°C.

[0079] Preferably, different types of substrates in the present invention include heavily doped Si substrates and flexible mica substrates. The thin film prepared by the present invention is used in the manufacture of devices (semiconductors). Si substrates are substrates currently required for semiconductor preparation. Almost all chips are Si substrates, on which circuits and small functional devices are etched. The Si substrate is used to combine all small devices. Therefore, when preparing the thin film, the present invention directly uses the Si substrate, so that the prepared thin film can be more easily applied to chips; flexible mica is used because some chips require practical operations such as bending, and placing electronic devices on a flexible substrate is the focus of current global technology, so the present invention selects mica as a flexible substrate to make a thin film.

[0080] The HCO film with ZrO2 intercalation layer obtained by the preparation method of the present invention uses ZrO2 as the intercalation layer, and the dielectric constant of ZrO2 obtained by the preparation method of the present invention is as high as 25, and has good insulation properties. Therefore, by inserting ZrO2 as an intercalation layer in the HCO film and regulating the position of the intercalation layer in the film, the ferroelectricity of the HCO film can be improved and / or the leakage performance of the film can be improved at the same time.

[0081] like Figure 2 As shown, the ZrO2 intercalation layer is located at the bottom position, the middle position, and the bottom and middle position of the HCO film. 1-x Ce x Taking O2 as 0.15 as an example, specific comparative examples and embodiments are given for illustration.

[0082] Comparative Example 1

[0083] Preparation of HCO thin film material on heavily doped Si substrate, the specific preparation steps are as follows:

[0084] (1) According to the chemical formula Hf 0.85 Ce 0.15 O2, weigh 0.5038g of hafnium acetylacetonate according to the stoichiometric ratio and dissolve it in acetic acid, heat and stir at 50℃ for 20min, and wait for the solution to become clear;

[0085] (2) According to the stoichiometric ratio, weigh 0.0651 g of cerium nitrate hexahydrate, dissolve it in the solution of (1), and stir at room temperature for 20 min until it is dissolved and clear;

[0086] (3) Acetylacetone and acetic acid were mixed in a ratio of 2:3, and the corresponding amount of acetylacetone was added and stirred in a water bath at 60°C for 30 min, and stirred at room temperature for 6 h. After standing for 48 h, Hf 0.85 Ce 0.15 O2 sol;

[0087] (4) Cut the heavily doped Si substrate into 8 mm*8 mm squares and ultrasonically clean them with acetone and anhydrous ethanol for 30 min respectively to remove oil and impurities on the surface of the substrate;

[0088] (5) Use a glue machine to mix Hf 0.85 Ce 0.15 The O2 sol was spin-coated on the heavily doped Si substrate at a low speed of 500 r / s and a high speed of 3000 r / s to obtain a wet film;

[0089] (6) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0090] (7) Based on step (6), steps (5) and (6) are repeated 5 times to obtain a Hf layer with a preset thickness of about 50 nm. 0.85 Ce 0.15 O2 film;

[0091] (8) Performing high temperature annealing treatment on the film of preset thickness in N2 atmosphere, the treatment temperature is 400°C, the holding time is 5 minutes, and then the temperature is raised to 800°C, and the holding time is 5 minutes;

[0092] (9) Use a vacuum coating apparatus to sputter a Pt electrode with a diameter of 0.2 mm on the surface of the film for subsequent electrical performance testing.

[0093] The above comparative example 1, in which no ZrO2 is added, is used for comparison with the following examples.

[0094] Comparative Example 2

[0095] Preparation of HCO thin film material on flexible mica substrate, the specific preparation steps are as follows:

[0096] (1) According to the chemical formula Hf 0.85 Ce 0.15 O2, weigh 0.5038g of hafnium acetylacetonate according to the stoichiometric ratio and dissolve it in acetic acid, heat and stir at 50℃ for 20min, and wait for the solution to become clear;

[0097] (2) According to the stoichiometric ratio, weigh 0.0651 g of cerium nitrate hexahydrate, dissolve it in the solution of (1), and stir at room temperature for 20 min until it is dissolved and clear;

[0098] (3) Acetylacetone and acetic acid were mixed in a ratio of 2:3, and the corresponding amount of acetylacetone was added and stirred in a water bath at 60°C for 30 min, and stirred at room temperature for 6 h. After standing for 48 h, Hf 0.85 Ce 0.15 O2 sol;

[0099] (4) Wipe the mica substrate with the ITO bottom electrode with anhydrous ethanol to remove the oil and impurities on the surface of the substrate. In the experiment, the mica substrate itself is not conductive, and the film needs electrodes (Pt electrodes) on the bottom and top to test the electrical properties. Therefore, in this step, a mica substrate with an ITO bottom electrode is used; the heavily doped Si itself is conductive, so no bottom electrode is required;

[0100] (5) Use a glue machine to mix Hf 0.85 Ce 0.15 The O2 sol was spin-coated on a mica substrate with an ITO electrode at a low speed of 500 r / s and a high speed of 3000 r / s to obtain a wet film;

[0101] (6) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0102] (7) Based on step (6), steps (5) and (6) are repeated 5 times to obtain a Hf layer with a preset thickness of about 50 nm. 0.85 Ce 0.15 O2 film;

[0103] (8) Performing high temperature annealing treatment on the film of preset thickness in N2 atmosphere, the treatment temperature is 400°C, the holding time is 5 minutes, and then the temperature is raised to 800°C, and the holding time is 5 minutes;

[0104] (9) Use a vacuum coating apparatus to sputter a Pt electrode with a diameter of 0.2 mm on the surface of the film for electrical performance testing.

[0105] The above comparative example 2 does not contain ZrO2 and is used for comparison with the following examples.

[0106] Example 1

[0107] Preparation of ZrO2-HCO thin film material on heavily doped Si substrate, the specific preparation steps are as follows:

[0108] (1) According to the chemical formula Hf 0.85 Ce 0.15 O2, weigh 0.5038g of hafnium acetylacetonate according to the stoichiometric ratio and dissolve it in acetic acid, heat and stir at 50℃ for 20min, and wait for the solution to become clear;

[0109] (2) According to the stoichiometric ratio, weigh 0.0651 g of cerium nitrate hexahydrate, dissolve it in the solution of (1), and stir at room temperature for 20 min until it is dissolved and clear;

[0110] (3) Acetylacetone and acetic acid were mixed in a ratio of 2:3, and the corresponding amount of acetylacetone was added and stirred in a water bath at 60°C for 30 min, and stirred at room temperature for 6 h. After standing for 48 h, Hf0.85 Ce 0.15 O2 sol;

[0111] (4) According to the chemical formula ZrO2, 0.4976 g of zirconium acetylacetonate was weighed and dissolved in acetic acid according to the stoichiometric ratio, and the mixture was stirred until clear. Then, a corresponding amount of acetylacetone was added, and acetylacetone and acetic acid were mixed in a ratio of 2:3. The mixture was stirred in a water bath at 60° C. for 30 min, and at room temperature for 6 h. After standing for 48 h, a ZrO2 sol was obtained.

[0112] (5) Cut the heavily doped Si substrate into 8 mm*8 mm squares and ultrasonically clean them with acetone and anhydrous ethanol for 30 min respectively to remove oil and impurities on the surface of the substrate;

[0113] (6) Using a coating machine, the ZrO2 sol is spin-coated on a heavily doped Si substrate at a low speed of 500 r / s and a high speed of 4000 r / s to obtain a wet film;

[0114] (7) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0115] (8) Use a glue machine to mix Hf 0.85 Ce 0.15 The O2 sol was continuously spin-coated on the ZrO2 film at a low speed of 500 r / s and a high speed of 3000 r / s to obtain a wet film;

[0116] (9) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0117] (10) Based on step (9), steps (8) and (9) are repeated 5 times to obtain a ZrO2-HCO film with a preset thickness of about 60 nm;

[0118] (11) subjecting the film of preset thickness to high temperature annealing treatment in N2 atmosphere at a treatment temperature of 400°C for 5 min, then heating to 800°C for 5 min;

[0119] (12) A Pt electrode with a diameter of 0.2 mm was sputtered on the surface of the film using a vacuum coating apparatus for electrical performance testing.

[0120] Example 2

[0121] Preparation of HCO-ZrO2-HCO thin film material on heavily doped Si substrate, the specific preparation steps are as follows:

[0122] (1) According to the chemical formula Hf 0.85 Ce 0.15O2, weigh 0.5038g of hafnium acetylacetonate according to the stoichiometric ratio and dissolve it in acetic acid, heat and stir at 50℃ for 20min, and wait for the solution to become clear;

[0123] (2) According to the stoichiometric ratio, weigh 0.0651 g of cerium nitrate hexahydrate, dissolve it in the solution of (1), and stir at room temperature for 20 min until it is dissolved and clear;

[0124] (3) Acetylacetone and acetic acid were mixed in a ratio of 2:3. After adding the corresponding amount of acetylacetone, stir in a water bath at 60°C for 30 min, stir at room temperature for 6 h, and stand for 48 h until Hf 0.85 Ce 0.15 O2 sol;

[0125] (4) According to the chemical formula ZrO2, 0.4976 g of zirconium acetylacetonate was weighed and dissolved in acetic acid according to the stoichiometric ratio, and the mixture was stirred until clear. Then, a corresponding amount of acetylacetone was added, and acetylacetone and acetic acid were mixed in a ratio of 2:3. The mixture was stirred in a water bath at 60° C. for 30 min, and at room temperature for 6 h. After standing for 48 h, a ZrO2 sol was obtained.

[0126] (5) Cut the heavily doped Si substrate into 8 mm*8 mm squares and ultrasonically clean them with acetone and anhydrous ethanol for 30 min respectively to remove oil and impurities on the surface of the substrate;

[0127] (6) Use a glue machine to mix Hf 0.85 Ce 0.15 The O2 sol was spin-coated on the heavily doped Si substrate at a low speed of 500 r / s and a high speed of 3000 r / s to obtain a wet film;

[0128] (7) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0129] (8) Based on step (7), repeat steps (6) and (7) twice;

[0130] (9) Using a spin coater, the ZrO2 sol is spin-coated on the HCO film at a low speed of 500 r / s and a high speed of 4000 r / s to obtain a wet film;

[0131] (10) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0132] (11) Based on step (10), steps (6) and (7) were repeated three times to obtain a HCO-ZrO2-HCO film with a thickness of 60 nm;

[0133] (13) subjecting the film of preset thickness to high temperature annealing treatment in N2 atmosphere at a treatment temperature of 400°C for 5 min, then heating to 800°C for 5 min;

[0134] (14) A Pt electrode with a diameter of 0.2 mm was sputtered on the surface of the film using a vacuum coating apparatus for electrical performance testing.

[0135] Example 3

[0136] Preparation of ZrO2-HCO-ZrO2-HCO thin film material on heavily doped Si substrate, the specific preparation steps are as follows:

[0137] (1) According to the chemical formula Hf 0.85 Ce 0.15 O2, weigh 0.5038g of hafnium acetylacetonate according to the stoichiometric ratio and dissolve it in acetic acid, heat and stir at 50℃ for 20min, and wait for the solution to become clear;

[0138] (2) According to the stoichiometric ratio, weigh 0.0651 g of cerium nitrate hexahydrate, dissolve it in the solution of (1), and stir at room temperature for 20 min until it is dissolved and clear;

[0139] (3) Acetylacetone and acetic acid were mixed in a ratio of 2:3, and the corresponding amount of acetylacetone was added and stirred in a water bath at 60°C for 30 min, and stirred at room temperature for 6 h. After standing for 48 h, Hf 0.85 Ce 0.15 O2 sol;

[0140] (4) According to the chemical formula ZrO2, 0.4976 g of zirconium acetylacetonate was weighed and dissolved in acetic acid according to the stoichiometric ratio, and the mixture was stirred until clear. Then, a corresponding amount of acetylacetone was added, and acetylacetone and acetic acid were mixed in a ratio of 2:3. The mixture was stirred in a water bath at 60° C. for 30 min, and at room temperature for 6 h. After standing for 48 h, a ZrO2 sol was obtained.

[0141] (5) Cut the heavily doped Si substrate into 8 mm*8 mm squares and ultrasonically clean them with acetone and anhydrous ethanol for 30 min respectively to remove oil and impurities on the surface of the substrate;

[0142] (6) Using a coating machine, the ZrO2 sol is spin-coated on a heavily doped Si substrate at a low speed of 500 r / s and a high speed of 4000 r / s to obtain a wet film;

[0143] (7) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0144] (8) Use a glue machine to mix Hf 0.85 Ce 0.15The O2 sol was continuously spin-coated on the ZrO2 film at a low speed of 500 r / s and a high speed of 3000 r / s to obtain a wet film;

[0145] (9) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for min;

[0146] (10) Based on step (9), repeat steps (8) and (9) twice;

[0147] (11) Using a spin coater, the ZrO2 sol is spin-coated on the HCO film at a low speed of 500 r / s and a high speed of 4000 r / s to obtain a wet film;

[0148] (12) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0149] (13) Based on step (12), steps (8) and (9) were repeated three times to obtain a film with a thickness of 70 nm;

[0150] (14) The film of preset thickness is subjected to high temperature annealing treatment in a N2 atmosphere at a treatment temperature of 400°C for a holding time of 5 min, and then the temperature is raised to 800°C for a holding time of 5 min.

[0151] (15) A Pt electrode with a diameter of 0.2 mm was sputtered on the surface of the film using a vacuum coating apparatus for electrical performance testing.

[0152] Example 4

[0153] Preparation of ZrO2-HCO-ZrO2-HCO thin film material on flexible mica substrate, the specific preparation steps are as follows:

[0154] (1) According to the chemical formula Hf 0.85 Ce 0.15 O2, weigh 0.5038g of hafnium acetylacetonate according to the stoichiometric ratio and dissolve it in acetic acid, heat and stir at 50℃ for 20min, and wait for the solution to become clear;

[0155] (2) According to the stoichiometric ratio, weigh 0.0651 g of cerium nitrate hexahydrate, dissolve it in the solution of (1), and stir at room temperature for 20 min until it is dissolved and clear;

[0156] (3) Acetylacetone and acetic acid were mixed in a ratio of 2:3. After adding the corresponding amount of acetylacetone, the mixture was stirred in a water bath at 60°C for 30 min, stirred at room temperature for 6 h, and allowed to stand for 48 h to obtain Hf 0.85 Ce 0.15 O2 sol;

[0157] (4) According to the chemical formula ZrO2, 0.4976 g of zirconium acetylacetonate was weighed and dissolved in acetic acid according to the stoichiometric ratio, and the mixture was stirred until clear. Then, a corresponding amount of acetylacetone was added, and acetylacetone and acetic acid were mixed in a ratio of 2:3. The mixture was stirred in a water bath at 60° C. for 30 min, and at room temperature for 6 h. After standing for 48 h, a ZrO2 sol was obtained.

[0158] (5) Wipe the mica substrate with the ITO bottom electrode clean with anhydrous ethanol to remove oil and impurities on the surface of the substrate.

[0159] (6) using a coating machine, spin coating the ZrO2 sol on a mica substrate with an ITO electrode at a low speed of 500 r / s and a high speed of 4000 r / s to obtain a wet film;

[0160] (7) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0161] (8) Use a glue machine to mix Hf 0.85 Ce 0.15 The O2 sol was continuously spin-coated on the ZrO2 film at a low speed of 500 r / s and a high speed of 3000 r / s to obtain a wet film;

[0162] (9) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0163] (10) Based on step (9), repeat steps (8) and (9) twice;

[0164] (11) Using a spin coater, the ZrO2 sol is spin-coated on the HCO film at a low speed of 500 r / s and a high speed of 4000 r / s to obtain a wet film;

[0165] (12) The wet film was placed in a rapid annealing furnace, dried at 180°C for 3 min, and pyrolyzed at 350°C for 3 min;

[0166] (13) Based on step (12), steps (8) and (9) were repeated three times to obtain a film with a thickness of 70 nm;

[0167] (14) subjecting the film of preset thickness to high temperature annealing treatment in N2 atmosphere at a treatment temperature of 400°C for 5 min, then heating to 800°C for 5 min;

[0168] (15) A Pt electrode with a diameter of 0.2 mm was sputtered on the surface of the film using a vacuum coating apparatus for electrical performance testing.

[0169] As can be seen from Examples 1-4, ZrO2-HCO thin films can be prepared on heavily doped Si substrates. Figure 2 (a) shows; HCO-ZrO2-HCO film, such as Figure 2 (b) as shown; ZrO2-HCO-ZrO2-HCO film, such as Figure 2 (c) As shown; a ZrO2-HCO-ZrO2-HCO film can be prepared on a flexible mica substrate, but the film prepared by the method of the present invention is not limited to the above-mentioned ones, and can also have other laminated structures, all of which are within the protection scope of the present invention.

[0170] in conclusion

[0171] The above Examples 1-4 were prepared according to the method of the present invention with ZrO2 as an intercalation layer at different positions of the HCO film. The films prepared with ZrO2 as an intercalation layer at different positions were characterized for electrical properties. The polarization-voltage curve and leakage current curve of these films were obtained using a ferroelectric test analyzer. Specifically, the prepared films were used as samples. Each group of samples was tested at least 8 times, and the large error data was removed, and the average value of other data was calculated to ensure the reliability of the results. The test results are as follows:

[0172] Figure 2 (a) indicates that the ZrO2 intercalation is located at the bottom of the film, (b) indicates that the ZrO2 intercalation is located in the middle of the film, and (c) indicates that the ZrO2 intercalation is located at the bottom and middle of the film. Figure 3 , 4 5 and 5 show the electrical properties test data of the thin film without ZrO2 intercalation prepared by the comparative example and the thin film with ZrO2 intercalation prepared by the embodiment, to illustrate the influence of ZrO2 intercalation and its different positions on the performance of the thin film.

[0173] Figure 3 The figure shows the comparison of polarization-voltage curves of Comparative Example 1 and Examples 1, 2, and 3 on a heavily doped Si substrate. The results show that the position of the ZrO2 intercalation layer has a great influence on the ferroelectric properties of the film. Specifically, when the ZrO2 intercalation layer is set at the bottom layer of the film or exists only at the bottom layer of the film, compared with the HCO film without intercalation layer in Comparative Example 1, the residual polarization intensity P of the film is r When ZrO2 intercalation exists in the middle of the film and ZrO2 intercalation exists in the middle and bottom of the film, the residual polarization strength of the film is greatly improved compared with the film generated in Comparative Example 1. Specifically, when ZrO2 intercalation is not added in Comparative Example 1, the residual polarization P of the generated HCO film is r ≈22μC / cm 2 , the remnant polarization P of the film of Example 1 r ≈24μC / cm 2 ; Remanent polarization P of the film of Example 2 r ≈37.5μC / cm2 ; Remanent polarization P of the film of Example 3 r ≈38μC / cm 2 , the optimal P after adding ZrO2 intercalation r Up to 38μC / cm 2 , increased by about 73%. Therefore, it is shown that when the ZrO2 intercalation layer is set in the middle position during the preparation of the film (regardless of whether there is a ZrO2 thin intercalation layer at the bottom at this time), the ferroelectric properties of the prepared film can be greatly improved.

[0174] Figure 4 The current density-voltage comparison of Comparative Example 1 and Examples 1-3 on a heavily doped Si substrate. The results show that Comparative Example 1 is a HCO film prepared without ZrO2 intercalation, and its leakage current is 10 -2 μA / cm 2 In Example 1-3, when ZrO2 is intercalated at the bottom of the HCO film, the leakage current is reduced to 10 -3 μA / cm 2 When ZrO2 is intercalated in the middle of the HCO film, the leakage current is almost the same as that without intercalation, which is 10 -2 μA / cm 2 When ZrO2 intercalation exists at the bottom and in the middle of the HCO film, the leakage current is 10 -3 μA / cm 2 Therefore, adding a thin ZrO2 intercalation layer at the bottom of the prepared HCO film (regardless of whether there is a ZrO2 thin intercalation layer in the middle of the HCO film at this time) greatly improves the leakage performance.

[0175] Figure 5 The polarization-voltage curves of Comparative Example 2 and Example 4 on a flexible mica substrate show that the effect of ZrO2 intercalation on the ferroelectric properties of thin films is also applicable on a flexible mica substrate. The thin film prepared in Comparative Example 2 is not intercalated with ZrO2, so the residual polarization P r =15μC / cm 2 ; After adding ZrO2 intercalation at the bottom and in the middle of the HCO film prepared in Example 4, the polarization P of the film r =30μC / cm 2 , which is increased by about 100% compared with the non-intercalated film in comparative example 2, greatly enhancing the ferroelectric properties of the prepared film.

[0176] The above conclusions indicate that whether a growth structure of alternating layers of ZrO2 and HCO is adopted on a heavily doped Si substrate or a flexible mica substrate, especially when the ZrO2 intercalation layer is arranged at the bottom of the film, or both at the bottom and in the middle, the ferroelectric properties of the HCO film produced can be effectively improved; when a thin ZrO2 intercalation layer is added to the bottom of the HCO film, the leakage performance is greatly improved. Therefore, the HCO film produced by the present invention is beneficial to the structural optimization design and performance improvement when the film is applied to electronic components.

[0177] The present invention provides a HCO film with a ZrO2 intercalation layer, which is prepared by the preparation method of the present invention. The HCO film has excellent ferroelectric properties and / or improved leakage properties.

[0178] The present invention also provides a cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer. 1-x Ce x The application of O2 film in new ferroelectric memory. The above embodiments show that the film prepared by the method of the present invention has excellent ferroelectric properties and / or improves the leakage performance at the same time. Therefore, it can be applied to new high-performance ferroelectric memory. The higher residual polarization strength of the film can effectively improve the read and write window of the memory, and the reduced leakage can effectively increase the service life of the memory.

[0179] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not depart from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation 1-x Ce x The method for preparing an O2 thin film is characterized in that: The method comprises the steps of: S1. Mix hafnium acetylacetonate, acetic acid, cerium nitrate hexahydrate and a chelating agent to obtain cerium hafnium oxide Hf 1-x Ce x O2 sol, where 0 <x<1; S2. The zirconium acetylacetonate, acetic acid and a chelating agent are mixed to obtain a ZrO2 sol; The S2 specifically includes: S21. Take zirconium acetylacetonate as the solute, dissolve it in acetic acid solution, stir at 40-60°C for 10-30min, and dissolve all the solute until it is clear; S22. Add an appropriate amount of chelating agent to the solution obtained in S21, heat in a water bath for 20-40 min, stir at room temperature for 4-8 h, and obtain ZrO2 sol after aging; S3. The Hf 1-x Ce x O2 sol and ZrO2 sol are coated on a substrate to obtain a wet film, wherein the substrate is a heavily doped Si substrate or a flexible mica substrate, and the Hf 1-x Ce x The concentration of O2 sol is 0.1-0.3 mol / L, and the concentration of ZrO2 sol is 0.1-0.3 mol / L; S4. pyrolysis treatment of the wet film; S5. Based on step S4, repeat steps S3 and S4 to obtain a cerium hafnium oxide Hf1- x Ce x O2 film.

2. The cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer according to claim 1 1-x Ce x The method for preparing an O2 thin film is characterized in that: The S1 specifically includes: S11. Dissolve hafnium acetylacetonate in acetic acid solution, stir at 40-60°C for 10-30 min, and dissolve all the solute until it is clear; S12. Weigh a certain amount of cerium nitrate hexahydrate and pour it into the solution obtained in S11, stir at room temperature for 10-30 minutes until the solute is completely dissolved and clear; S13. Add an appropriate amount of chelating agent to the solution obtained in S12, heat in a water bath for 20-40 minutes, and stir at room temperature for 4-8 hours to obtain Hf 1-x Ce x The O2 sol is aged for 24-72 hours in a greenhouse environment.

3. The cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer according to claim 1 or 2 1-x Ce x The method for preparing an O2 thin film is characterized in that: The chelating agent is acetylacetone.

4. The cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer according to claim 1 1-x Ce x The method for preparing an O2 thin film is characterized in that: The invention also includes S6. adding the cerium hafnium oxide Hf with a preset thickness of zirconium oxide ZrO2 intercalation layer 1-x Ce x The O2 film was annealed at high temperature in a N2 atmosphere.

5. The cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer according to claim 1 or 2 1-x Ce x The method for preparing an O2 thin film is characterized in that: The preset thickness is 50-100 nm.

6. The cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer according to claim 1 1-x Ce x The method for preparing an O2 thin film is characterized in that: The value range of x is 0.11 to 0.

16.

7. A cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation 1-x Ce x O2 thin film, characterized in that The film is prepared by the preparation method described in any one of claims 1 to 6.

8. A cerium hafnium oxide Hf with zirconium oxide ZrO2 intercalation layer as claimed in claim 7 1-x Ce x Application of O2 thin films in ferroelectric memory.

Citation Information

Patent Citations

  • Hafnium oxide-based ferroelectric film structure based on Van der Waals force effect and preparation method thereof

    CN115172588A